2010
DOI: 10.1073/pnas.1008533107
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin-dependent light avoidance in neonatal mice

Abstract: Melanopsin-expressing, intrinsically photosensitive retinal ganglion cells (ipRGCs) form a light-sensitive system separate from rods and cones. Direct light stimulation of ipRGCs can regulate many nonimageforming visual functions such as photoentrainment of circadian rhythms and pupil responses, and can intensify migraine headache in adults. In mice, ipRGCs are light responsive as early as the day of birth. In contrast, their eyelids do not open until 12-13 d after birth (P12-13), and light signaling from rods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
128
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 43 publications
8
128
0
1
Order By: Relevance
“…For nonimage vision, although adaptation is certainly beneficial for increasing the signaling dynamic range, the exact implication of Weber-Fechner behavior is less obvious. Because ipRGCs are now known to also contribute to conscious vision (12,(48)(49)(50)(51)(52), this adaptation behavior may have more to do with the latter function. It would, thus, be useful to know whether the other ipRGC subtypes [which supposedly are more involved in image vision compared with M1 cells (12,15)] show similar adaptation behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For nonimage vision, although adaptation is certainly beneficial for increasing the signaling dynamic range, the exact implication of Weber-Fechner behavior is less obvious. Because ipRGCs are now known to also contribute to conscious vision (12,(48)(49)(50)(51)(52), this adaptation behavior may have more to do with the latter function. It would, thus, be useful to know whether the other ipRGC subtypes [which supposedly are more involved in image vision compared with M1 cells (12,15)] show similar adaptation behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been shown that light exposure induces avoidance behavior in early postnatal mice (12), light stimuli may increase stress levels of the pups, potentially affecting granule cell migration. Therefore, to comprehensively understand the role of light stimuli in granule cell migration and cerebellar development, it is necessary to examine what degree of light exposure may induce toxic effects on the proliferation, migration, and differentiation of immature neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Even though mice do not open their eyes until approximately postnatal day 12 (P12), it has been reported that light stimuli induce physiological changes well before that time (12). In early postnatal mouse cerebella, granule cell precursors proliferate actively at the top of the external granular layer (EGL) (13).…”
mentioning
confidence: 99%
“…By P14 (eye opening), slow activity and rapid activity alternate in cortex with arousal state and sensory input. (Johnson et al, 2010) and electrophysiological Kirkby and Feller, 2013) effects before P8, when we first observed N2. Furthermore, synaptic blockade in retina eliminates visual responses in rats at equivalent ages .…”
Section: High Lowmentioning
confidence: 99%